2015
DOI: 10.1016/j.juro.2015.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Lymphatic Metastases in Upper Tract Urothelial Carcinoma and Proposed Dissection Templates

Abstract: Purpose Information on patterns of lymph node metastases (LNM) for upper tract urothelial carcinoma (UTUC) is sparse. We investigate patterns of LNM in UTUC. Materials/Methods Retrospective multi-institutional study of 73 patients with N+M0 UTUC undergoing template lymphadenectomy during nephroureterectomy. Anatomic locations of tumor, number of lymph nodes removed, positive lymph nodes were analyzed and descriptive statistics performed. Results On right side: renal pelvis tumors (n=20) had LNM to the hilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…This issue was identified in our study as significant variation existed in the number of LNs resected by each individual surgeon at the same institution. Recent nodal mapping efforts by Matin et al 19 , which add to previous work by Kondo et al 20 , thoroughly detailed the predicted landing zones of LN metastases according to the laterality and location of the tumor. Such efforts aid in the development of anatomical templates that can be implemented both for standardization of surgical dissection and potentially improved oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This issue was identified in our study as significant variation existed in the number of LNs resected by each individual surgeon at the same institution. Recent nodal mapping efforts by Matin et al 19 , which add to previous work by Kondo et al 20 , thoroughly detailed the predicted landing zones of LN metastases according to the laterality and location of the tumor. Such efforts aid in the development of anatomical templates that can be implemented both for standardization of surgical dissection and potentially improved oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multi-institutional study of 73 pN1 patients, the majority of patients with right-sided renal pelvic and proximal ureteric tumors were found to have hilar and paracaval LN metastases, whereas those with left-sided tumors most often had metastases to the hilar and paraaortic LNs. 19 Involvement of the interaortocaval LNs was common in patients with right-sided tumors and paracaval LN metastases but not those with left-sided tumors. Although validation of these findings is required, an earlier observational study that compared patients with UTUC undergoing RNU with and without LND using templates similar to those described in the study above reported that patients with muscle-invasive (pT2) renal pelvic tumors who received template-based LND had a higher CSS compared to those treated with RNU alone.…”
Section: Discussionmentioning
confidence: 94%
“…Matin el al. [38] performed a retrospective multi-institutional study in a larger cohort undergoing template disecction, showing right to left as well as cranial migration, and suggesting templates. For example, on the right side, resection of the hilar, paracaval and retrocaval LNs would identify 82.9% of LN metastases, while adding Interaortocaval LNs would increase that to 95.8%.…”
Section: Methodsmentioning
confidence: 99%
“…LND appears to confer a survival benefit in those with high-risk disease. More recent data [38] highlights the reduction in locoregional recurrence when an adequate LND is performed. In the only meta-analysis published in the literature [39] about the effect of lymph node dissection on the outcomes of UTUC, there was a better CSS in patients with muscle invasive UTUC receiving LDN vs. non-LDN (HR: 2.19) and better CSS in pN0 vs. pNx.…”
Section: Methodsmentioning
confidence: 99%